The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1007/s004410051221
|View full text |Cite
|
Sign up to set email alerts
|

The distribution and ultrastructure of class II MHC-positive cells in human dental pulp

Abstract: The distribution and ultrastructure of class II major histocompatibility complex (MHC)-positive cells were investigated in human dental pulp, employing immunohistochemistry using an anti-human leukocyte antigen (HLA)-DR-monoclonal antibody. HLA-DR-immunopositive cells, appearing spindle-like or dendritic in profile, were densely distributed throughout the dental pulp. Under the electron microscope, these cells exhibited various sizes of vesicles containing clear or opaque contents, multivesicular bodies and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 24 publications
(37 reference statements)
0
28
0
Order By: Relevance
“…These class II MHC-positive cells along the pulp-dentin border were characterized by tubulovesicular structures and multivesicular bodies, as categorized in the pulpal dendritic cells described above (Ohshima et al, 1994(Ohshima et al, , 1999. This phenomenon may be explained by the idea that the pulpal dendritic cells respond actively to bacterial or noxious substances derived through the exposed dentinal tubules, as we have suggested .…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…These class II MHC-positive cells along the pulp-dentin border were characterized by tubulovesicular structures and multivesicular bodies, as categorized in the pulpal dendritic cells described above (Ohshima et al, 1994(Ohshima et al, , 1999. This phenomenon may be explained by the idea that the pulpal dendritic cells respond actively to bacterial or noxious substances derived through the exposed dentinal tubules, as we have suggested .…”
Section: Discussionmentioning
confidence: 70%
“…Interestingly, under experimental conditions, the class II MHC-positive cells have been suggested to have diverse functions in odontoblast differentiation in the rat dental pulp in addition to ordinary antigen presentation . Under physiological conditions, furthermore, class II MHC-positive cells in the human odontoblast layer and/or predentin might have some regulatory function in the homeostasis of odontoblasts (Ohshima et al, 1999). These findings, therefore, lead us to the possibility that the immunocompetent cells play an important role in the process of pulpal healing after cavity preparation.…”
Section: Introductionmentioning
confidence: 96%
“…13 Although the function of these cells is not clearly understood, anatomical proximity and functional coupling through gap junctions implies a regulatory role. 14 Interodontoblastic cells could be involved in the response of odontoblasts to bacterial challenge, and they may be necessary for an integrated response to bacterial invasion.…”
mentioning
confidence: 99%
“…Dendritic cells show no or little activity of acid phosphatase (ACP), whereas macrophages have phagocytic capability and exhibit ACP activity that is dependent on the phagocytic capability (Steinman et al 1986). Class II MHC antigen-expressing cells have been identified in the dental pulp of humans and rats by immunohistochemistry using HLA-DR and OX-6 antibodies (Jontell et al 1987(Jontell et al , 1988(Jontell et al , 1991(Jontell et al , 1994Ohshima et al 1994Ohshima et al , 1995Ohshima et al , 1999Okiji et al 1994Okiji et al , 1996Okiji et al , 1997Yoshiba et al 1996). Based on the criteria of the expression of class II MHC antigens and the activity of ACP, previous studies have indicated that, whereas macrophages are present in the central region of the dental pulp, dendritic cells are located in and around the odontoblastic layer.…”
Section: Introductionmentioning
confidence: 98%
“…The immunological aspects in pulpal tissue and the putative function of these cells were reviewed by Jontell et al (1998). It has been suggested that the class II MHC-expressing dendritic cells in the odontoblastic layer may regulate the function of odontoblasts and play a role in odontoblast differentiation in human and rat teeth (Ohshima et al 1995(Ohshima et al , 1999, and class II MHC-positive cells have been suggested to play an inductive role in differentiation, migration, and/or activation of odontoblasts and cementoblast-like cells during the resorption stage of human deciduous teeth (Kannari et al 1998). In addition, age-related change and delayed appearance of class II MHC-positive cells have been reported in dental pulp during development of rat incisors and molars (Jontell et al 1991;Okiji et al 1996).…”
Section: Introductionmentioning
confidence: 99%